A bio-inspired stimulator to desynchronize epileptic cortical population models: A digital implementation framework. (July 2015) - Piri, Mohsen; Amiri, Masoud; Amiri, Mahmood
Abstract: Pathophysiologic neural synchronization is a hallmark of several neurological disorders such as epilepsy. In addition, based on established neurophysiologic findings, astrocytes dynamically regulate the synaptic transmission and have key roles in stabilizing neural synchronization. Therefore, in the present study, based on the dynamic model of astrocyte, a digital bio-inspired stimulator is proposed to avoid the hyper-synchronous seizure-like activities in a cortical population model. The complete digital circuit of the close loop system that is the bio-inspired stimulator and the cortical population model are implemented in hardware on the ZedBoard development kit. Based on the results of MATLAB simulations, hardware synthesis and FPGA implementation, it is demonstrated that the digital bio-inspired stimulator can effectively prevent the occurrence of spontaneous paroxysmal episodes with a demand-controlled characteristic. In this way, the designed digital stimulator successfully maintains the normal ongoing activity.